“Doing it Our Way” Participation and Kinship in Traditional Surrogacy Narratives in Aotearoa New Zealand - Hannah Grace Gibson (University of Edinburgh Library, 2021)
The practice of traditional surrogacy gives rise to multiple discourses around women’s autonomy and kinship practices globally. In the Aotearoa New Zealand context, traditional surrogacy (where the surrogate donates her own egg as well as gestating the foetus) is legal only on an altruistic basis. Furthermore, it is subject to neither medical nor state oversight, unlike gestational surrogacy which is heavily regulated. Drawing on three years of ethnographic research, this article focuses on both traditional surrogates in Aotearoa New Zealand who have children of their own and those who have chosen a childfree life. Their narratives reveal multilayered motivations that align with and diverge from the ‘help’ narrative often associated with altruistic surrogacy. By drawing on and contributing to current debates on surrogacy globally, I show that traditional surrogates take on their role with clear ideas about kinship and different interpretations of reproductive participation. Their narratives bring to the fore the under-researched topic of traditional surrogacy, and in particular of women who do not want children of their own but choose to donate their eggs and gestate the foetus for another woman. I argue that their negotiation of stigma to make/resist kin disrupts pervasive heteronormative modes of kinship.